Graphene reinforced cement composites: A review. (30th December 2020) - Lin, Youli; Du, Hongjian
Highlights: Capabilities of graphene reinforced concrete are reviewed. Reinforcing mechanism is assessed for graphene in concrete. Graphene concrete has great potential to build smart and sustainable city. Main directions and barriers for future research and applications are identified. Abstract: Graphene reinforced cement composites have been continuously reported in the past years to exhibit extraordinary mechanical properties, durability and multi-functionality owing to the unique intrinsic properties possessed by pristine graphene. In this review paper, a critical and synthetical overview of recent research findings of the graphene reinforced cement composites was conducted. The review will discuss the techniques for the dispersion of graphene and the influence of graphene on rheology, hydration, microstructure, mechanical properties, autogenous shrinkage, durability, electrical and thermal properties of cement composites. The main challenges and future prospects of graphene reinforced cement composites will be discussed to provide constructive ideas and guidance to assist with relevant studies in future.